Heteroleptic tris-chelate ruthenium(II) complexes of N,N-disubstituted-N '-acylthioureas: Synthesis, structural studies, cytotoxic activity and confocal microscopy studies - Barolli, Joao P.; Maia, Pedro I. S.; Colina-Vegas, Legna; Moreira, Jane [UNESP]; Plutin, Ana M.; Mocelo, Raul; Deflon, Victor M.; Cominetti, Marcia R.; Camargo-Mathias, Maria I. [UNESP]; Batista, Alzir A. (Elsevier B.V., 2017)
Ruthenium complexes have been assessed as anti-tumor agents against cancer cells. In this project, new heteroleptic rutheniuM(II) complexes with general formulae [Ru(L)(bipy)(dppb)](PF6) (where L = N,N-disubstituted-N'-acylthiourea, bipy = 2,2'-bipyridine and dppb = 1,4-bis(diphenylphosphino)butane) were synthesized and characterized by elemental analysis, IR and NMR and (H-1 and P-31{H-1}) spectroscopies, molar conductivity measurements and single crystal X-ray diffractometry. The IR and NMR data suggest the coordination of the ligands to the Ru(II) metal center through the tfiiocarbonyl and carbonyl groups. The structures of the new complexes were further studied by X-ray crystallography, which confirmed the coordination of the ligands with the metal through the sulfur and oxygen atoms, leading to the formation of distorted octahedral complexes. The N,N-disubstituted-N'-acylthioureas and their complexes were screened with respect to their in vitro cytotoxicity. All compounds exhibited considerable antipro-liferative activity against MCF-7 (human breast tumor cells ATCC HTB-26), DU-145 (human prostate tumor cells ATCC HTB-26), and relatively low toxicity against fibroblast L929 cells (health cell line from mouse ATCC CCL-1). A preliminary study regarding the mechanism of action of these compounds by con focal microscopy shows alterations of the actin filaments leading to Modifications in cytoskeletal supporting the cell death and that the cell nucleus is not main target of these complexes. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Acylthiourea derivatives; Crystal structures; Ruthenium complexes; Antiproliferative activity; Confocal microscopy